Adsorption of aqueous selenite [Se(IV)] species on synthetic layered double hydroxide materials - Mandal, Sujata; Mayadevi, S.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2009)
{Layered double hydroxide materials (Zn/Al, Mg/Al, Zn/Fe) with varying composition (M(2+):M(3+) molar ratio